Damage detection in a three-dimensional laboratory tower model using modal correlation coefficient algorithm - Barros, Ammiel Mac A.
Structural health monitoring is vital in checking and maintaining structural integrity, and one of its key components is damage detection. This can be accomplished by visual inspection but as in the usual case, it is impractical to inspect each member of a complex structure, and hence as an alternative, another method must be employed - damage detection through modal analysis. Modal Correlation Coefficient (MCC) is a type of the latter method and it is based on the changes in mode shape of the damaged and the undamaged structure, with emphasis on the abrupt changes in the slope of the mode shape. For this study, a two-meter-high truss tower was used in the implementation of MCC. Three cases of damage was introduced through the replacement of members with different Elastic Modulus. The structure's undamaged and damaged modal properties was obtained both in the Finite Element Method, and using the Operational Modal Analysis. Both of these were then used in the MCC algorithm. Results showed that MCC was able to detect the damage in all three cases examined.